Recent Developments in Nano Based Hair Dye Formulations and their Characterizations (International Journal of Food and Nutritional Sciences, 2022)
The recent developments in nanoscience and nanotechnology have opened up newpossibilities for permanent dye hair applications. Since 2000, a lot of reports are coming onthe synthesis of nano-based hair dye formulations. Mainly, three strategies are involved in thesynthesis of nano-based hair dyes: (i) Nanoparticle based hair dyes, (ii) Graphene and carbonnanotube-based hair dyes and (iii) Melanin biomimicking based hair dyes. Nanoparticlebased dyes, due to their increased surface area, can penetrate well into hair follicles. Thereare reports of gold, silica and PbS nano particle-based hair dye formulations, but theirpotential commercial application as hair dyes is limited due to various factors like multiplesynthesis steps, time needed for developing color and low color fastness.Even though,graphene based hair dye is promising, the color range is limited. Development of hair dyeformulations by biomimicking melanine synthesis by chemoenzymatic methods has recentlyreceived attention by the scientific community.Considerable amount of work has so far beencarried out with polydopamine (one of the synthetic eumelanines) based multicolor systemsfor hair dyeing